2021
DOI: 10.1002/saj2.20200
|View full text |Cite
|
Sign up to set email alerts
|

A regional soil classification framework to improve soil health diagnosis and management

Abstract: , 530-333-7925 CORE IDEAS  Soil health research needs to develop diagnostics tailored to regional groupings of soils  Cluster analysis of a soil survey database revealed groups distinct from U.S. Soil Taxonomy  Inherent structure in soil survey data serves as a means to guide soil health investigations  Seven soil health regions were identified in California  Soil survey data classification framework shows promise for place-based soil health approaches ABSTRACT Soil health research has developed soil test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…However, discretization makes it possible to calculate a cumulative normal curve or parameterize algorithms with fewer observations to generate a suitable scoring curve. With these drawbacks in mind, a recent study demonstrated that applying soil survey data to unsupervised machine learning can classify soils to reflect natural differences in soil properties and characteristics in the western United States (Devine et al, 2020). However, this technique was not applied to calibrating soil health assessment scores.…”
Section: Summary Of Assessment Composite Scoresmentioning
confidence: 99%
“…However, discretization makes it possible to calculate a cumulative normal curve or parameterize algorithms with fewer observations to generate a suitable scoring curve. With these drawbacks in mind, a recent study demonstrated that applying soil survey data to unsupervised machine learning can classify soils to reflect natural differences in soil properties and characteristics in the western United States (Devine et al, 2020). However, this technique was not applied to calibrating soil health assessment scores.…”
Section: Summary Of Assessment Composite Scoresmentioning
confidence: 99%
“…Soil health regions tend to be, but are not necessarily, geographically contiguous, as a result of soil forming factors. Regions were defined in this study using K-means clustering of the Soil Survey Geographic (SSURGO) database and were shown to be distinct from USDA-NRCS Soil Taxonomy (Devine et al 2021).…”
Section: Soil Health Regions Frameworkmentioning
confidence: 99%
“…To better understand regional soil patterns in California, the USDA-NRCS Soil Survey Geographic (SSURGO) database was grouped into regions of "soil health identity" in California sharing similar inherent soil properties (Devine et al 2021). Using this recently published framework, the main objective of this study was to examine effects of practices that improve or maintain soil health in different regions.…”
Section: K-means Clusteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil classification is a routine approach for grouping soils based on their intrinsic property, behavior, or genesis with broad applications to soil science, particularly pedometry, soil survey, and soil mapping. In the literature, grouping soils has been performed on the basis of similarities in taxonomic (Devine et al., 2021; Pachepsky & Rawls, 1999), textural (García‐Gutiérrez et al., 2018; Pachepsky & Park, 2015), and structural (Nguyen et al., 2015; Rawls & Pachepsky, 2002a) properties. For example, the Natural Resource Conservation Service (NRCS, 1986) classified soils into four hydrologic groups based on the soil's runoff potential.…”
Section: Introductionmentioning
confidence: 99%